Deepwater overflow observed by three bottom-anchored moorings in the Bashi Channel. (April 2016) - Zhao, Xiaolong; Zhou, Chun; Zhao, Wei; Tian, Jiwei; Xu, Xiaobiao
Abstract: Three moorings equipped with 10 current meters and 7 CTDs were deployed in the Bashi Channel, the main deep connection between the northwestern Pacific Ocean and the South China Sea, from August 2010 to April 2011 to investigate the deepwater overflow of the North Pacific Deep Water through it. Results from these observations provide, for the first time, valuable information on the spatial structure of the deep current and allow us to estimate the overflow transport with greater accuracy. The observed current is coherent both vertically and horizontally but exhibits a much stronger velocity in the central area compared to near the edges of the channel. The core of the overflow is found near 2600 m, with mean velocity, potential temperature, and salinity of 22.5 cm s −1, 1.79 °C, and 34.64 psu, respectively. The current is approximately geostrophic, with isopycnals sloping upward to the right-hand side of the flow. The local Froude number is found much less than 1, implying that the deep flow in the Bashi Channel could not be hydraulically controlled. The observations yield an 8-month mean transport of 0.78 Sv with an rms error of 0.18 Sv. The transport time series exhibits significant intraseasonal variabilities, including variability on time scale close to the resonance period of the deep channel in the Luzon Strait ( 30 days). Higher transports are connected with a higher velocity and a thicker overflow layer, allowing colder and saltier (thus denser) North Pacific Deep Water to flow into the South China Sea. Highlights: Deepwater overflow through the Bashi Channel is investigated based on three moorings. The observations show a much stronger current in the middle of the channel. Time mean volume transport is estimated and temporal variability is discussed.